1994
DOI: 10.1093/infdis/169.3.680
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Delayed Hypersensitivity in Chlamydia trachomatis Salpingitis in Monkeys: A Pathogenic Mechanism of Tubal Damage

Abstract: The role of delayed hypersensitivity in the pathogenesis of Chlamydia t trachomatis salpingitis was studied in the monkey "pocket" model. Pigtailed monkeys (Macaca nemestrina) were sensitized by inoculation of live C. trachomatis organisms (E/UW-5/Cx) into subcutaneous pockets containing salpingeal autotransplants. At 21 days, affinity-purified recombinant C. trachomatis heat-shock protein (rhsp60) was injected into pockets either previously sensitized with C. trachomatis or not sensitized in the same monkey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 10 publications
3
52
0
1
Order By: Relevance
“…However, both methods are costly and invasive, and therefore unsuitable for screening on a large scale. Since tubal pathology and infertility have been associated with asymptomatic Chlamydia trachomatis infections in the past, chlamydia antibody testing (CAT) in serum has been introduced as a screening method for tubal factor subfertility [7][8][9][10]. Hence the development of a simple and reliable assay for the detection of C. trachomatis antibodies is essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, both methods are costly and invasive, and therefore unsuitable for screening on a large scale. Since tubal pathology and infertility have been associated with asymptomatic Chlamydia trachomatis infections in the past, chlamydia antibody testing (CAT) in serum has been introduced as a screening method for tubal factor subfertility [7][8][9][10]. Hence the development of a simple and reliable assay for the detection of C. trachomatis antibodies is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Later Morrison and coauthors [36,37] demonstrated that a 57-kDa protein, identified as chlamydial HSP60, is the active component and responsible for the inflammatory response in trachoma. Experimental studies in the monkey`pocket' model of salpingitis have further supported the role of HSP60-specific T cells in the pathogenesis of salpingitis [38].…”
Section: Hsp60 Specific T-cell Response In Animalsmentioning
confidence: 92%
“…1 Adanya heat shock protein 60 (hsp) Chlamydia, reaksi imun tipe lambat serta pelepasan sitokin merupakan mekanisme yang menimbulkan kerusakan pada tuba fallopi. 2,3 Prevalensi infeksi C. trachomatis pada wanita Eropa berkisar 1,7-17%. 4 Pada wanita infertil, prevalensi infeksi ini lebih tinggi.…”
Section: Pendahuluanunclassified